DEMOGRAPHIC DISTRIBUTION AND CONSTRAINTS TO FISH CATCH AND LIVELIHOOD OF FISHERS IN SELECTED MAN-MADE LAKES IN OYO STATE, NIGERIA - Oladapo, O. O.; Ajani , E. K. (Nigerian Journal of Fisheries, 2024)
This research examined the demographical distribution of fishers and constraints to fish catch and livelihood of fishers in selected Man-made lakes in Oyo State, Nigeria. Cross-sectional studies were carried out among 162 respondents in five selected man-made lakes in Oyo state, using structured questionnaires. A total enumeration method was used to examine all the registered fishers on the selected lakes and the data collected were analysed using descriptive statistics and a Likert scale. The respondents were dominated by males with 92.6% and the mean age was 47.19 years. Years of fishing experience had 11-20 years as the highest frequency with 39.5% of the respondents, while secondary school education led among the educational status with 42.0% of the respondents. The majority of the respondents (93.8%) were married and 79.0% had one wife. The average number of children of the respondents was three and the household size average was five. Meanwhile, 72.2% of the respondents were practising as part-time fishers. Among the listed constraints to fish catch and livelihoods by the majority of the fishers, lack of access to capital (58.0%), pollution of water bodies (46.9%), costly fishing materials (69.1%), glut (50.6%), inadequate storage facilities (75.3%), primitive preservation methods (64.2%) and proliferation of aquatic weeds (82.7%) were noted as very severe constraints. The existence of a large number of part-time fishers pointed out that fishing is not sufficient for the livelihoods of the respondents and it is therefore, important for government and non-governmental agencies to assist the fishers with their constraints, especially the very severe ones